TINGKAT PEMAHAMAN MASYARAKAT TERHADAP PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) DI KOTA TARAKAN - Ana Sriekaningsih; Slamet Riyanto; Andre Prakasa (GEMILANG: Jurnal Manajemen dan Akuntansi, 2022)
The purpose of this study was to analyze the level of understanding of the QRIS community, to analyze the use of QRIS, to analyze the community's response to the convenience of QRIS and to analyze the public response to the socialization of the Indonesian Standard Quick Response Code (QRIS) in Tarakan City. The analytical technique used in this study uses a qualitative research approach. The results showed that the level of public understanding of the Quick Response Code Indonesian Standard (QRIS) in Tarakan City was quite good. The use of the Indonesian Standard Quick Response Code (QRIS) in Tarakan City is quite good and many people have used QRIS. The community's response showed interest in using QRIS after knowing its function, felt interested in using it, was not interested in using it and had used QRIS. And the community response from the QRIS socialization was also quite good.